\[\boxed{\text{480\ (480).}\text{\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
Пояснение.
Решение.
\[1)\ 2a^{3} - 3a^{2} - 2ab + 3b =\]
\[= a^{2} \cdot (2a - 3) - b \cdot (2a - 3) =\]
\[= (2a - 3) \cdot \left( a^{2} - b \right)\]
\[если\ a = 0,5;\ \ \ \ \ b = 2,25:\]
\[(2 \cdot 0,5 - 3) \cdot \left( {0,5}^{2} - 2,25 \right) =\]
\[= (1 - 3) \cdot (0,25 - 2,25) =\]
\[= - 2 \cdot ( - 2) = 4.\]
\[2)\ xy + y^{2} - 12x - 12y =\]
\[= y \cdot (x + y) - 12 \cdot (x + y) =\]
\[= (x + y) \cdot (y - 12)\]
\[если\ x = 10,8;\ \ \ \ y = - 8,8:\]
\[(10,8 - 8,8) \cdot ( - 8,8 - 12) =\]
\[= 2 \cdot ( - 20,8) = - 41,6.\]
\[3)\ 27x^{3} - 36x^{2} + 6x - 8 =\]
\[= 9x^{2} \cdot (3x - 4) + 2 \cdot (3x - 4) =\]
\[= (3x - 4) \cdot \left( 9x^{2} + 2 \right)\]
\[при\ x = - 1\frac{1}{3} = - \frac{4}{3}:\]
\[\boxed{\text{480.}\text{\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[1)\ (x - y) \cdot \ *\ = x^{2}y^{2} - x^{3}y\]
\[(x - y) \cdot \ *\ = - x^{3}y + x^{2}y^{2}\]
\[(x - y) \cdot \ *\ = - x^{2}y \cdot x + x^{2}y \cdot y\ \]
\[(x - y) \cdot \ * = - x^{2}y(x - y)\]
\[*\ = - x^{2}\text{y.}\]
\[2)\ \left( - 9x^{2} + \ * \right) \cdot y = \ * + y^{4}\]
\[- 9x^{2} \cdot y + *_{1} \cdot y = *_{2} + y^{4}\]
\[- 9x^{2} \cdot y = *_{2}\]
\[*_{1} \cdot y = y^{4}\]
\[*_{2} = - 9x^{2} \cdot y\]
\[*_{1} = \frac{y_{4}}{y} = y^{3}.\]
\[3)\ (1,4x - *) \cdot 3x = \ * - 0,6x^{3}\]
\[1,4x \cdot 3x - *_{1} \cdot 3x = *_{2} - 0,6x^{3}\]
\[4,2x^{2} - *_{1} \cdot 3x = *_{2} - 0,6x^{3}\]
\[4,2x^{2} = *_{2}\]
\[*_{1} \cdot 3x = 0,6x^{3}\]
\[*_{1} = \frac{0,6x^{3}}{3x} = 0,2x^{2}.\]
\[*_{2} = 4,2x^{2};\ \ \ \ \ *_{1} = 0,2x^{2}.\]
\[4)*\ \cdot \left( * - x^{2}y^{5} + 5y^{6} \right) =\]
\[= 8x^{3}y^{3} + 5x^{3}y^{8} - \ *\]
\[*_{1} \cdot *_{2} + *_{1} \cdot \left( - x^{2}y^{5} \right) + *_{1} \cdot 5y^{6} =\]
\[= 8x^{3}y^{3} + 5x^{3}y^{8} - *_{3}\]
\[1)*_{1} \cdot *_{2} = 8x^{3}y^{3}\]
\[2) - *_{1} \cdot x^{2}y^{5} = 5x^{3}y^{8}\]
\[3)*_{1} \cdot 5y^{6} = - *_{3}\]
\[*_{1} \cdot 5y^{6} = - *_{3}\]
\[*_{1} = \frac{5x^{2}y^{8}}{- x^{2}y^{5}} = - 5xy^{3}\]
\[*_{1} = - 5xy^{3}\]
\[*_{1} \cdot *_{2} = 8x^{3}y^{3}\]
\[- 5xy^{3} \cdot *_{2} = 8x^{3}y^{2}\]
\[*_{2} = \frac{8x^{3}y^{3}}{- 5xy^{3}} = - 1,6x^{2}\]
\[*_{3} = *_{1} \cdot 5y^{6}\]
\[*_{3} = - 5xy^{3} \cdot 5y^{6} = - 25xy^{9}.\]